Precision excision of mandibular anterior compound odontoma using autonomous robotic guidance: a clinical case report - Di, Tiankai; Liu, Chen; Liu, Yuhan; Bai, Shizhu; Wu, Li-an; Chen, Yujiang; Zhao, Yimin (Frontiers in Oral Health, 2025)
BackgroundManagement of compound odontomas in the pediatric anterior mandible poses significant surgical challenges due to proximity to developing tooth follicles and neurovascular structures. Conventional enucleation risks iatrogenic injury to adjacent dentoalveolar anatomy, while suboptimal bone preservation may impede permanent tooth eruption.Case descriptionAn 8-year-old patient presented with a compound odontoma adjacent to the unerupted permanent mandibular incisor. Utilizing an autonomous robotic guidance system independently developed by our research group, we performed minimally invasive enucleation featuring: (1) virtual osteotomy pathway planning, (2) sub-millimeter precision bone removal preserving the follicular space of tooth 31, and (3) capsule dissection under optical navigation. At the 2-week follow-up, the surgical site demonstrated complete mucosal healing without neurosensory complications, and CBCT confirmed absence of residual pathology.ConclusionRobotic-assisted enucleation enabled tissue-preserving removal of a high-risk odontoma while maintaining eruption potential. This approach represents a paradigm shift toward precision-targeted dentoalveoral surgery, particularly valuable for anatomically complex pediatric cases.Clinical Trial Registrationidentifier [ChiCTR2400092822].